Acidosis during maximal performance in front crawl swimming over distances of 100 m to 400 m - Strumbelj, B.; Usaj, A.; Kapus, V.; Bednarik, J.; Kapus, N. (Biomechanics and Medicine in Swimming IX, 2003)
INTRODUCTION During competition in the front crawl swimming energy production is derived from the aerobic system and from anaerobic glycolyisis. The amount of anaerobic glycolysis is dependent upon the distance and velocity at which the swims are performed. Acidosis in the organism causes several effects associated with fatigue: inhibition of phosphofructokinase and slow glycolysis, H+ may act do displace Ca2+ from troponin, low pH may stimulate pain receptors and H+ can inhibit the combination of O2 with hemoglobin in the lung. The purpose of this study was to ascertain if a change experinced by a swimmer exerting maximal effort in a competition, visible in what is probably a limiting acidosis, is the factor which prevents the swimmer going faster. METHODS Six swimmers (average age 22±9yrs, height 184±8cm and weight 72± 6kg), participated in this study. Each swimmer performed a maximal front crawl swim on the distances of 100 m, 200 m, 300 m and 400 m on separate days. Arterialysed blood samples (20 ml) were collected from the hear-lob after warm up, at 1,3, 5 and 7 minute of recovery from swimming and analysed for blood lactate [LA], pH and Pco2. Means and standard deviations were computed for all variables. The results were analyzed using paired t-test for small samples. RESULTS For the model of maximal swims we can observe that the mean velocity was on 100 m very high and with increasing distance signifficantly decreased. [LA] signifficantly increased only from warm up to 100 m and from 300 m to 400 m. On the distances between 100 m and 300 m we found no signifficant differences in [LA] (Picture 1.). Simmilar results were obtained for pH. The values of Pco2 slightlly increased in comparision with valu es after warm up on all the distances from 100 m to 400 m however not signifficantly. DISCUSSION In comparision with other studies which compared data of [LA] obtained on the various distances with different subject sample, were signifficant differences between various disciplines were found (Bonifazi et al. 1993), we found that if we compare individual values of [LA] a certain individual [LA] exists which probably limits maximal performance. This [LA] values are obtained alredy on the distance of 100 m freestyle and are very different from subject to subject.